The Impact of Generic Clopidogrel Bisulfate on Platelet Inhibition in Patients with Coronary Artery Stents: Results of the ACCEL-GENERIC Study - Jeong, Young-Hoon; Koh, Jin-Sin; Kang, Min-Kyung; Ahn, Yeon-Jeong; Kim, In-Suk; Park, Yongwhi; Hwang, Seok-Jae; Kwak, Choong Hwan; Hwang, Jin-Yong (The Korean journal of internal medicine, 2010)
In patients with coronary artery stents, the cost of clopidogrel has been cited as a factor in the premature discontinuation of therapy. Thus, the introduction of lower-cost generic clopidogrel may increase patient compliance. However, platelet inhibition by generic clopidogrel has not been compared to the original clopidogrel formulation in patients with coronary artery stents. We prospectively enrolled 20 patients receiving chronic therapy with the original clopidogrel bisulfate (Plavix). After assessing patient compliance with Plavix, maintenance therapy was switched to generic clopidogrel bisulfate (Plavitor). Platelet reactivity was assessed at baseline and 30-day after the switch using conventional aggregometry and the VerifyNow P2Y12 assay. All patients completed maintenance therapy with Plavitor. Before and after switching therapy maximal (36.5 +/- 7.9% vs. 39.8 +/- 16.2%, p = 0.280) and late platelet aggregation (23.5 +/- 10.9% vs. 29.1 +/- 18.3%, p = 0.156) with 5 micromol/L adenosine diphosphate (ADP) stimulus did not differ. Likewise, 20 micromol/L ADP-induced platelet aggregation and P2Y12 reaction unit in patients on Plavitor therapy was comparable to that in patients on Plavix therapy. However, Bland-Altman analysis showed wide limits of agreement between measured platelet reactivity on Plavix vs. Plavitor therapies. Among patients on Plavix maintenance therapy with coronary stents, replacement with Plavitor shows a comparable inhibition of ADP-induced platelet aggregation. However, due to poor inter-therapy agreement, between two regimens, physicians may be cautious when introducing generic clopidogrel bisulfate.